Загальні принципи вибору моделей і середовищ моделювання водозбірних басейнів - Костріков, С.В. (Кримський науковий центр НАН України і МОН України, 2005)
This paper revises some of basic fundamentals for the proper model type selection in case of watershed modeling. General approaches to the implementation of the common computer modeling methodology are applied to the given area of expertise. A digital elevation model and a geoinformation model of watershed are compared and characterized. The author has analyzed the standardized computer modeling environment separately. Finally the relevant software sample has been represented and briefly discussed together with its application to the real topographic area in a watershed.